Examination of the leisure involvement and leisure constraints levels of individuals doing ski and snowboard as a recreational physical activity - Davut Budak; Neslihan Kandil (Atatürk University, 2024)
This study aimed to examine the levels of leisure involvement and perceived leisure constraints of individuals who ski and snowboard based on various characteristics. The study group of research consisted of 796 individuals (Mage=32.48±12.82) who ski/snowboard in 5 ski resorts in Turkey. In the research, "Leisure Involvement Scale" (LIS) and "Leisure Constraints Scale" (LCS) were used as data collection tools. MANOVA, and ANOVA analyses were used to analyze the collected data. According to the MANOVA results with regard to gender, there were statistically significant differences between the average scores of the groups in all subscales of the "LIS" except the "interpersonal constraints" subscale of the "LCS". There was no significant difference between the participants' "LCS" mean scores according to the education level variable. On the other hand, it was found that there were statistically significant differences in all subscales of the "LIS" of the participants concerning the education level. The average scores of participants with master's/doctoral education were found to be higher than others in all subscales where differences were observed. According to the results of the analysis based on the activity type variable of the participants, there are significant differences only in the "intrapersonal factors" of the "LCS" and all subscales of the "LIS". MANOVA analysis results revealed that the average scores of the participants in all subscales of "LCS", "interpersonal constraints" "intrapersonal constraints" and "LIS" differed significantly according to the variable of having their materials. As a result, it was concluded that the most important factor that constrained individuals from participating in ski and snowboard sports as a leisure activity was "structural factors". In addition, it has been found that the three most important reasons why individuals are interested in skiing or snowboarding or both as winter sports are "attraction, "social bonding" and "centrality", respectively.